The body keeps the score : brain, mind, and body in the healing of trauma - Van der Kolk, Bessel A., 1943- (New York, New York : Viking, 2014)
An expert on traumatic stress outlines an approach to healing, explaining how traumatic stress affects brain processes and how to use innovative treatments to reactivate the mind's abilities to trust, engage others, and experience pleasure--
Facing trauma -- The rediscovery of trauma. Lessons from Vietnam veterans ; Revolutions in understanding mind and brain ; Looking into the brain : the neuroscience revolution -- This is your brain on trauma. Running for your life : the anatomy of survival ; Body-brain connections ; Losing your body, losing your self -- The minds of children. Getting on the same wavelength : attachment and attunement ; Trapped in relationships : the cost of abuse and neglect ; What's love got to do with it? ; Developmental trauma : the hidden epidemic -- The imprint of trauma. Uncovering secrets : the problem of traumatic memory ; The unbearable heaviness of remembering -- Paths to recovery. Healing from trauma : owning your self ; Language : miracle and tyranny ; Letting go of the past: EMDR ; Learning to inhabit your body : yoga ; Putting the pieces together : self-leadership ; Filling in the holes : creating structures ; Rewiring the brain : neurofeedback ; Finding your voice : communal rhythms and theater -- Epilogue : Choices to be made -- Appendix. Consensus proposed criteria for developmental trauma disorder.
Includes bibliographical references (pages [363]-421) and index.
Keywords: Post-traumatic stress disorder -- Treatment; Stress Disorders, Post-Traumatic -- Physiopathology; Stress Disorders, Post-Traumatic -- therapy; Psychic trauma -- Treatment; Mind and body